THE ROLE OF FOREIGN LANGUAGE PROFICIENCY IN CONTEMPORARY EDUCATION - Ro’zmetova Maftuna Rasulovna (Bright Mind Publishing, 2025)
In a globalized world where intercultural communication and international collaboration are increasingly vital, proficiency in foreign languages has become an essential asset. This article discusses about the necessity of foreign language acquisition through cognitive, educational, cultural, and economic lenses. Drawing on contemporary research, it argues that multilingualism is no longer a luxury but a foundational skill for global citizenship, academic success, and professional development.
Keywords: Necessity, language, English, foreign languages, skills, multilingualism.